Project Evaluation of Transportation Projects: an Application of Financial Computable General Equilibrium Model - Euijune Kim; Geoffrey J.D. Hewings; Hidayat Amir (European Regional Science Association (ERSA), 2015)
We develop a Financial Computable General Equilibrium Model (FCGE) model that can analyse the economic impacts of the infrastructure investment projects and their financing options on growth and distribution in Indonesia economy. It is possible to estimate growth and distributional effects of each project based on the financing method (government financing with tax revenues, government bond, and private financing) over the construction and operation periods if the information on the investment expenditures, the construction location and the accessibility of the project are injected into the FCGE model. The government financing with tax revenues could generate higher effects on GDP than two other financing methods regardless of projects. However, the presented values of benefits over costs are less than one for two sample highway projects, so they cannot be sustainable with regard to economic assessment.
Keywords: C68; D58; H54; O18; 330; Transportation Investment; Infrastructure Policy; Financial CGE Model